Numerical investigation on natural convection of hybrid nanofluid Al2O3 – MWCNT/water inside a vertical annulus. Issue 1 (May 2021) - Usmani, Raheel; Hussain, F; Khan, SA; Khan, NA; Khan, U; Husain, S
Abstract: A numerical inspection on natural convection inside a vertical annulus interior of which water based (Al2 O3 + MWCNT) (7:3) hybrid nanofluid has presently been carried out using CFD solver Ansys Fluent. Finite volume method (FVM) is used to perform the numerical simulations at constant heat flux of 3kW/m 2 and various volume fraction (0-0.04) of nanoparticle. The thermal conductivity and viscosity of hybrid nanofluid is computed by modified Maxwell model and Batchelor model respectively. The paper carried explicit analysis on effect of nanoparticle concentration, Nu number and heat transfer coefficient. The maximum enhancement in average heat transfer coefficient found to be 73.67% when gauged on volume fraction of 0.04.